Funkcjonowanie zintegrowanego systemu zapewniania jakości na przykładzie wybranego zakładu gastronomicznego - praca przeglądowa - Kowalczyk, Marta; Lesiów, Tomasz (Functioning of Quality Assurance Integrated System on the Example of Chosen Leading Gastronomic Company- a Review, 2008)
The aim of the paper is to present specific functioning of Food Safety Management System integrating HACCP with a system of Quality Management according to ISO 9001 in gastronomy, i.e. on the basis of activities of a leading company in this area. The authors discuss the most important differences between food industry and gastronomy in functioning of Food Safety Management System, organization and technology production of gastronomic products and health hazards which can appear during production of meals in gastronomy. The authors emphasize that food safety and assurance of its high quality in all stages of production and food trade depends on efficient functioning of integrated systems, i.e. each element in long food chains (the chain also includes employees). Integration of HACCP with Quality Management System according to ISO 9001 improves productivity, efficacy and efficiency in the area of food safety quality in comparison with systems functioning independently. Briefly, the idea and potential implication of Food Safety Management System according to ISO 22000 in gastronomy was presented. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 30, s. 62-81